Sustainability assessment of levulinic acid and succinic acid production from empty fruit bunch - Hafyan, R.H. (Institute of Physics Publishing, 2020)
Empty fruit bunch (EFB) generated as waste in plantation mill activities in Malaysia is a potential biomass feedstock of biorefinery for fuels and chemicals production. Levulinic acid and succinic acid, two out of 12 chemical building blocks identified by Department of Energy (DOE) to be used in synthesis of high-value materials, can be produced from biochemical conversion of the EFB. This paper evaluates sustainability assessment of EFB to levulinic acid and succinic acid. The assessments include net present value (NPV), global warming potential (GWP), and Hazard identification and ranking (HIRA) to cater for economic, environment, and safety performances, respectively. The results show that the levulinic acid production is more economically attractive than succinic acid production. The environmental impact quantification reveals that the levulinic acid has lower GWP score of 6.3 kgCO2-eq/kg levulinic acid than succinic acid with 11.2 kgCO2-eq/kg succinic acid. Meanwhile, the succinic acid production is inherently safer than levulinic acid production due to its less severe operating conditions. Â© 2020 IOP Publishing Ltd.